2015
DOI: 10.1523/jneurosci.2329-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Trace Fear Conditioning Differentially Modulates Intrinsic Excitability of Medial Prefrontal Cortex–Basolateral Complex of Amygdala Projection Neurons in Infralimbic and Prelimbic Cortices

Abstract: Neuronal activity in medial prefrontal cortex (mPFC) is critical for the formation of trace fear memory, yet the cellular mechanisms underlying these memories remain unclear. One possibility involves the modulation of intrinsic excitability within mPFC neurons that project to the basolateral complex of amygdala (BLA). The current study used a combination of retrograde labeling and in vitro whole-cell patch-clamp recordings to examine the effect of trace fear conditioning on the intrinsic excitability of layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 72 publications
4
71
4
Order By: Relevance
“…In contrast to our findings, a recent study found that trace fear conditioning increases the excitability of IL layer V neurons projecting to the amygdala (Song et al, 2015). There are several differences between the studies that could contribute to the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, a recent study found that trace fear conditioning increases the excitability of IL layer V neurons projecting to the amygdala (Song et al, 2015). There are several differences between the studies that could contribute to the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Altogether, these data indicate that mAHP is increased from 1 to 10 d of training in FosGFP Ϫ neurons, but not in FosGFP ϩ neurons, which corresponds with our previously observed decrease of intrinsic excitability in FosGFP Ϫ neurons from 1 to 10 d of training. SK channels are known to contribute to mAHP magnitude in cortical neurons (Alger et al, 1994;Sah and Faber, 2002). We used the selective SK channel antagonist apamin to study the role of SK channels in modulating the firing rate of FosGFP Ϫ PLC neurons from only the test group rats.…”
Section: Plc Neurons After Food Self-administrationmentioning
confidence: 99%
“…One possible scenario is that different neuronal ensembles intermingle within PLC that encode separate learned associations or memories (Warren et al, 2016). This seems likely given the diverse role of PLC in attentional allocation, contextual encoding, and rewarding and aversive learning (Watanabe, 1996;Schall et al, 2002;Fujii and Graybiel, 2003;Euston et al, 2012;Sharpe and Killcross, 2014;Pinto and Dan, 2015). In support of this idea, recently, we demonstrated a critical role of infralimbic cortex (ILC) neuronal ensembles in both operant learning and extinction of the operant response (Warren et al, 2016).…”
Section: Intrinsic Excitability Alterations Within Fos-expressing Neumentioning
confidence: 99%
“…Within the mPFC, the infralimbic (IL) and prelimbic (PL) cortices are intimately implicated in fear extinction and fear acquisition respectively 21 . The IL and PL send strong inputs to the amygdala and may gate inputs from the BLA into the CeA 39,21,40 . The NAc and BLA have robust reciprocal connections.…”
Section: Background On Circuitry and Fearmentioning
confidence: 99%